Nephropathic Cystinosis: Symptoms, Treatment, and Perspectives of a Systemic Disease - Bäumner, Sören; Weber, Lutz T. (Frontiers in Pediatrics, 2018)
Cystinosis is a rare autosomal recessive lysosomal storage disorder caused by mutations in the CTNS gene. Main dysfunction is a defective clearance of cystine from lysosomes that leads to accumulation of cystine crystals in every tissue of the body. There are three different forms: infantile nephropathic cystinosis, which is the most common form, juvenile nephropatic and non-nephropathic cystinosis. Mostly, first symptom in infantile nephropathic cystinosis is renal Fanconi syndrome that occurs within the first year of life. Another prominent symptom is photophobia due to corneal crystal deposition. Cystine Depletion therapy with cysteamine delays end-stage renal failure but does not stop progression of the disease. A new cysteamine formulation with delayed-release simplifies the administration schedule but still does not cure cystinosis. Even long-term depletion treatment resulting in bypassing the defective lysosomal transporter cannot reverse Fanconi syndrome. A future perspective offering a curative therapy may be transplantation of CTNS-carrying stem cells that has successfully been performed in mice.